Baihe Dihuang Danshen Decoction Alleviates Myocardial Ischemia-Reperfusion Injury in Depression-Induced Rats by Inhibiting Ferroptosis - Huang, Ling; Liu, Cuihua; Liang, Yudan; Huang, Wenquan; Zhang, Shizhong; Xu, Qiang; Qiu, Kuncheng (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: NADPH/FSP1/CoQ10 pathway